Preclinical tumor control with a laser-accelerated high-energy electron radiotherapy prototype - Zhiyuan Guo; Shuang Liu; Bing Zhou; Junqi Liu; Haiyang Wang; Yifei Pi; Xiaoyan Wang; Yingyi Mo; Bo Guo; Jianfei Hua; Yang Wan; Wei Lu (Nature Communications)
Abstract Radiotherapy using very-high-energy electron (VHEE) beams (50-300 MeV) has attracted considerable attention due to its advantageous dose deposition characteristics, enabling deep penetration and easy manipulation by magnetic components. One promising approach to compactly delivering these high energy electron beams in a cost-effective manner is laser wakefield acceleration (LWFA), which offers ultra-strong accelerating gradients. However, the transition from this concept to a functional machine intended for tumor treatment remains elusive. Here we present the self-developed pro- totype for LWFA-based VHEE radiotherapy, exhibiting compactness (occupying less than 5 m2) and long-term operational stability (validated over a period of one month). Subsequently, we employ this device to irradiate a tumor implanted in a mouse model. Following a dose delivery of 5.8 ± 0.2 Gy with precise tumor conformity, all irradiated mice exhibit pronounced control of tumor growth. For comparison, this tumor-control efficacy is similar to that achieved using commercial X-ray radiotherapy equipment operating at equivalent doses. These results demonstrate a compact and stable laser-driven VHEE system dedicated for preclinical studies involving small animal models and its promising prospects for future clinical translation in cancer therapy.